Evaluating the impact of the Tissue Viability Seating guidelines. Issue 1 (February 2021) - Stephens, Melanie; Bartley, Carol; Samuriwo, Ray; Stubbs, Nikki
Abstract: Introduction: Internationally, guidelines are developed to ensure safe, effective, person centred, timely, efficient, and effective practice. However, their use in clinical practice is found to be variable. The Tissue Viability Society (TVS) published updated seating guidelines in 2017, yet, little is known about how these guidelines are being used. Methods: The aim of this evaluation was to gauge the impact of the Tissue Viability Seating Guidelines on clinical practice and policy. A cross-sectional questionnaire was used to elicit the responses from anyone with an interest or role within seating and pressure ulcer prevention and management. The survey was distributed through a variety of methods including email to members of the Tissue Viability Society and social media platforms from September to December 2019. Results: and Discussion: There were thirty-nine responses, the bulk of which were from healthcare professionals across primary and secondary care. All but one respondent was from the United Kingdom. Eleven had incorporated the latest TVS seating guidance into policy and sixteen into practice. The results of our survey demonstrates congruence with the literature as the main themes that emerged included incorporating the guidance into everyday clinical practice, education, and training, and as a resource or dissemination tool. Barriers to implementation included being unaware of the guidelines and unaware of one's own professional and collective organisational responsibility to guideline dissemination. However, many respondents were planning to incorporate the guidelines using a variety of methods. Conclusion: This survey has shown there are some examples of successful implementation of the TVS Seating guidelines. Future TVS guidelines should include implementation strategies, interventions, and goals for local champions to ensure barriers to implementation are both assessed and addressed. Future work could also include a trial of the guidelines within a pilot project. Highlights: Guideline use in clinical practice is found to be variable. Evaluations of the impact of clinical guidelines on clinical practice is necessary. Practitioners incorporate guidance into everyday clinical practice, education, and training. Guidelines are used as a resource or dissemination tool. Being unaware of guidelines and one's own professional and collective responsibility is a barrier.